Chronic kidney disease after liver transplantation in human immunodeficiency virus/hepatitis C virus–coinfected recipients versus human immunodeficiency virus–infected recipients without hepatitis C virus: Results from the national institutes of health multi‐site study. Issue 6 (28th May 2013) - Bahirwani, Ranjeeta; Barin, Burc; Olthoff, Kim; Stock, Peter; Murphy, Barbara; Rajender Reddy, K.; ,
<x xml:space="preserve">Abstract</x> Hepatitis C virus (HCV) and human immunodeficiency virus (HIV) are both associated with chronic kidney disease (CKD), a major complication after orthotopic liver transplantation (OLT). The aim of this study was to assess predictors of post‐OLT CKD in HIV/HCV‐coinfected recipients versus HIV‐infected recipients without HCV (HIV/non‐HCV recipients). Data from a National Institutes of Health study of 116 OLT recipients (35 HIV/non‐HCV recipients and 81 HIV/HCV‐coinfected recipients) from 2003 to 2010 (Solid Organ Transplantation in HIV: Multi‐Site Study) were analyzed for the pretransplant CKD prevalence [estimated glomerular filtration rate (eGFR) < 60 mL/minute for ≥3 months] and the incidence of CKD up to 3 years posttransplant. Proportional hazards models were performed to assess predictors of posttransplant CKD. A contemporaneous cohort of HCV‐monoinfected transplant recipients from the Scientific Registry of Transplant Recipients database was also analyzed. The median age at transplant was 48 years, the median serum creatinine level was 1.1 mg/dL, and the median eGFR was 77 mL/minute. Thirty‐four patients were suspected to have pretransplant CKD; 20 of these patients (59%) had posttransplant CKD. Among the 82 patients without pretransplant CKD (26 HIV/non‐HCV patients and 56 HIV/HCV‐coinfected patients), the incidence of stage 3 CKD 3 years after OLT was 62% (55% of HIV/non‐HCV patients and 65% of HIV/HCV‐coinfected patients), and the incidence of stage 4/5 CKD was 8% (0% of HIV/non‐HCV patients and 12% of HIV/HCV‐coinfected patients). In a multivariate analysis, older age [[hazard ratio (HR) = 1.05 per year, P = 0.03] and the CD4 count (HR = 0.90 per 50 cells/μL, P = 0.01) were significant predictors of CKD. HCV coinfection was significantly associated with stage 4/5 CKD (HR = 10.8, P = 0.03) after adjustments for age. The cumulative incidence of stage 4/5 CKD was significantly higher for HIV/HCV‐coinfected patients versus HIV/non‐HCV transplant recipients and HCV‐monoinfected transplant recipients (P = 0.001). In conclusion, CKD occurs frequently in HIV‐infected transplant recipients. Predictors of posttransplant CKD include older age and a lower posttransplant CD4 count. HCV coinfection is associated with a higher incidence of stage 4/5 CKD. Liver Transpl 19:619–626, 2013. © 2013 AASLD.